CONSEQUENCES OF EXTERNAL ENVIRONMENT ON ENTREPRENEURIAL MOTIVATION IN IRAN - Hassan Gholipour Fereidouni; Tajul Ariffin Masron; Davoud Nikbin; Reza Ekhtiari Amiri (Asian Academy of Management Journal, 2010)
The purpose of this study is to examine importance of business environment, social status of entrepreneurs, and country external conflicts as predictors of motivation to start a business in an environment, such as that in Iran, in which the economy is highly dependent on government initiatives. Data are collected from 106 MBA students through questionnaires. Respondents are questioned regarding the perceived importance of the business environment, socio-cultural factors (social status), and country external conflicts. The results show that the importance of business environment and country external conflicts contribute considerably to the level of entrepreneurial motivation. Further, the results reveal that social status is not a critical factor in determining the level of motivation to start a business. In particular, business environment is the most important factor in predicting entrepreneurial motivation. The results contribute to the growing body of literature in entrepreneurship and provide some implications for Iranian policy makers to create favourable external environment for potential entrepreneurs.